Tominaa Of Torajanese In Rambu Solo Funeral Ceremony - Ruben Ruru; Dahlia D. Moelier; Sudirman Maca (Fakultas Sastra, Universitas Bosowa, 2022)
The study aims at finding out the types and meaning of the Tominaa language or utterances that used in Rambu Solo text. The data were analyzed and transcribed into English. The sources of the data were the Rambu solo text and the explanation from the village leader who understands well the Tominaa language. The study applied the qualitative descriptive method. The study reveal that there were 20 data from Rambu solo text which told about the life journey history of the death peolple before she/he burying. The data were transcribed based on the information from informants but it was difficult to understand because some words have two meaning and only appears in particular time. Only a few informants who could understand perfectly about the text and its meaning the new generation of Tanah Toraja already forgot about this language.